2016
DOI: 10.5812/jjm.29645
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of the cadF Gene and Development of a Duplex Polymerase Chain Reaction for Species-Specific Identification of Campylobacter jejuni and Campylobacter coli

Abstract: BackgroundCampylobacteriosis is a zoonotic infectious disease caused by Campylobacter jejuni and C. coli. The cadF gene is considered as a genus-specific gene while other genes are mainly used for discrimination at the species level.ObjectivesThis study aimed to analyze the cadF gene and to develop a duplex PCR assay for simultaneous detection of C. coli and C. jejuni, the two commonly encountered species.Materials and MethodsIn silico analysis of the cadF gene was carried out by several software and available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…There are various other PCR assays published for species differentiation of C. jejuni and C. coli with and without detection of further Campylobacter spp 12,[24][25][26][27][28][29] . Thus, the whole-genome sequences of the strains leading to ambiguous species differentiation with mapA/ceuE targets 3,5 and the correctly identified C. coli hybrids with high C. jejuni content were further assessed in silico ( Supplementary Fig.…”
Section: Are the Strains With Ambiguous Qpcr Results Typable By Other mentioning
confidence: 99%
See 2 more Smart Citations
“…There are various other PCR assays published for species differentiation of C. jejuni and C. coli with and without detection of further Campylobacter spp 12,[24][25][26][27][28][29] . Thus, the whole-genome sequences of the strains leading to ambiguous species differentiation with mapA/ceuE targets 3,5 and the correctly identified C. coli hybrids with high C. jejuni content were further assessed in silico ( Supplementary Fig.…”
Section: Are the Strains With Ambiguous Qpcr Results Typable By Other mentioning
confidence: 99%
“…The sequence data revealed that also cpn60 detection 24 would lead to false species identification of all C. coli hybrid strains but would identify C. coli correctly in the "half hybrids", in which mapA/ceuE were no reliable targets. Besides, strain BfR-CA-17110 harboured a C. jejuni sequence in the target cadF 28,29 , leading to false C. jejuni identification of this C. coli strain. All other targets hipO, glyA, lpxA and ccoN displayed either no or low C. jejuni introgression.…”
Section: Are the Strains With Ambiguous Qpcr Results Typable By Other mentioning
confidence: 99%
See 1 more Smart Citation
“…They can be transmitted to humans through direct contact with animals, consumption of contaminated food and water, and unpasteurized milk [1,4]. Some gastrointestinal problems, called campylobacteriosis, especially in children have observed affected by Campylobacter jejuni [5][6][7]. CadF is one of the important proteins, a 37kDa protein as a conserved and genus-speci c outer membrane protein, that binds to bronectin and the bacterium attaches to the host cell, lead to facilitate colonization.…”
Section: Introductionmentioning
confidence: 99%
“…They can be transmitted to humans through direct contact with animals, consumption of contaminated food and water, unpasteurized milk or contact with patients [1,3]. Some gastrointestinal diseases are caused by this pathogen, which it has considered as one common bacterial cause of diarrhea, especially in children [1,[4][5][6]. According to researches, more than 229,000 cases of the campylobacteriosis have been reported worldwide [7].…”
Section: Introductionmentioning
confidence: 99%